Caspase-1-Mediated Activation of Interleukin-1β (IL-1β) and IL-18 Contributes to Innate Immune Defenses against Salmonella enterica Serovar Typhimurium Infection - Raupach, Bärbel (American Society for Microbiology, 2006)
Caspase-1 (Casp-1) mediates the processing of the proinflammatory cytokines interleukin-1β (IL-1β) and IL-18 to their mature forms. Casp-1-deficient mice succumb more rapidly to Salmonella challenge than do wild-type animals. Both Casp-1 substrates, IL-18 and IL-1β, are relevant for control of Salmonella enterica serovar Typhimurium. We used IL-18(−/−) and IL-1β(−/−) mice in addition to administration of recombinant IL-18 to Casp-1(−/−) mice to demonstrate that IL-18 is important for resistance to the systemic infection but not for resistance to the intestinal phase of the infection. This suggests that IL-1β is critical for the intestinal phase of the disease. Thus, we show that Casp-1 is essential for host innate immune defense against S. enterica serovar Typhimurium and that Casp-1 substrates are required at distinct times and anatomical sites.